2002
DOI: 10.1002/pits.10062
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among stressful life events, temperament, problem behavior, and global life satisfaction in adolescents

Abstract: The relationships among stressful life events (SLEs), temperament, externalizing and internalizing behaviors, and global life satisfaction were investigated. The Students' Life Satisfaction Scale, the Youth Self Report (YSR) form of the Child Behavior Checklist, a portion of the Life Events Checklist, and the Abbreviated Junior Eysenck Personality Questionnaire, were administered to 1,201 adolescents in grades 6 through 12 in a small city in the Southeast. A modest correlation was found between life satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
120
1
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 225 publications
(158 citation statements)
references
References 27 publications
21
120
1
8
Order By: Relevance
“…Similar findings have been reported among children and adolescents (e.g. Ash and Huebner 2001;Casas et al 2004;Greenspoon and Saklofske 2001;Heaven 1989;Huebner 1991a;McKnight et al 2002). For example, Fogle et al (2002) found LS to be positively correlated with extraversion and social self-efficacy, negatively correlated with neuroticism, and to mediate the relationship between LS and extraversion, but not between LS and neuroticism.…”
Section: Personality and Life Satisfactionsupporting
confidence: 64%
See 1 more Smart Citation
“…Similar findings have been reported among children and adolescents (e.g. Ash and Huebner 2001;Casas et al 2004;Greenspoon and Saklofske 2001;Heaven 1989;Huebner 1991a;McKnight et al 2002). For example, Fogle et al (2002) found LS to be positively correlated with extraversion and social self-efficacy, negatively correlated with neuroticism, and to mediate the relationship between LS and extraversion, but not between LS and neuroticism.…”
Section: Personality and Life Satisfactionsupporting
confidence: 64%
“…For example, Suldo and Huebner (2004b) demonstrated that LS mediates the relationship between the social support-involvement dimension of authoritative parenting and adolescent problem behaviour. Further, support has been provided for the potential mediating role of LS between stressful life events and internalizing behaviour (see McKnight et al 2002). In addition, there is recent evidence to suggest that increased LS buffers against the negative effects of stress and the development of psychological disorder.…”
Section: Life Satisfaction: More Than An Epiphenomenonmentioning
confidence: 99%
“…Life satisfaction reflects a sense of contentment and congruency between needs or wants and accomplishments (Keyes and Waterman 2003), and is conceptually and empirically distinguishable from positive and negative affect (McKnight et al 2002). …”
Section: Life Satisfaction In Young Peoplementioning
confidence: 99%
“…Life satisfaction has been identified as an important outcome for adolescents with and without disabilities (Huebner, 2004), and, as mentioned above, an important component of perceptions of subjective well-being (Diener et al, 2002) and quality of life (Huebner, 2004;Huebner, Suldo, Smith, & McKnight, 2004). Life satisfaction has also been related to school functioning (Huebner & Alderman, 1993;Huebner & McCullough, 2000) and a decreased likelihood of externalizing behaviors (McKnight, Huebner, & Suldo, 2002;Suldo & Huebner, 2004a, 2004b. Hope and optimism have, in previous research, been found to contribute to adolescent's life satisfaction (Edwards, 2004).…”
Section: Introductionmentioning
confidence: 99%